Mycorrhizal trifoliate orange has greater root adaptation of morphology and phytohormones in response to drought stress - Zou, Ying-Ning; Wang, Peng; Liu, Chun-Yan; Ni, Qiu-Dan; Zhang, De-Jian; Wu, Qiang-Sheng (Scientific reports, 2017)
Plant roots are the first parts of plants to face drought stress (DS), and thus root modification is important for plants to adapt to drought. We hypothesized that the roots of arbuscular mycorrhizal (AM) plants exhibit better adaptation in terms of morphology and phytohormones under DS. Trifoliate orange seedlings inoculated with Diversispora versiformis were subjected to well-watered (WW) and DS conditions for 6 weeks. AM seedlings exhibited better growth performance and significantly greater number of 1st, 2nd, and 3rd order lateral roots, root length, area, average diameter, volume, tips, forks, and crossings than non-AM seedlings under both WW and DS conditions. AM fungal inoculation considerably increased root hair density under both WW and DS and root hair length under DS, while dramatically decreased root hair length under WW but there was no change in root hair diameter. AM plants had greater concentrations of indole-3-acetic acid, methyl jasmonate, nitric oxide, and calmodulin in roots, which were significantly correlated with changes in root morphology. These results support the hypothesis that AM plants show superior adaptation in root morphology under DS that is potentially associated with indole-3-acetic acid, methyl jasmonate, nitric oxide, and calmodulin levels.
Keywords: kyseliny indoloctové; kalmodulin; Cyclopentanes; Adaptation, Physiological; Plant Growth Regulators; oxid dusnatý; Calmodulin; Nitric Oxide; cyklopentany; acetáty; oxylipiny; regulátory růstu rostlin; Oxylipins; kořeny rostlin; Mycorrhizae; Poncirus; Glomeromycota; fyziologická adaptace; Indoleacetic Acids; Acetates; období sucha; Droughts; Plant Roots; mykorhiza